Analysis on the prevalence and temporal trends of adverse birth outcomes among neonates in Shanghai from 2010 to 2023 - Yongfa Qin; Jia Zhao; Yiyuan Li; Jing Chen; Yin Dai; Hui Li; Tao Zhang; Zhe Sun; Ying Lu; Xue Han (Frontiers in Public Health, 2025)
BackgroundPrevious research has focused on the risk factors of adverse birth outcomes and its short-term and long-term consequences. However, study on the temporal trends of adverse birth outcomes is few. Furthermore, the population-level correlation between the rate of advanced maternal age (AMA) and the prevalence of adverse birth outcomes remains underexplored. This study aimed to provide the most recent temporal trends of adverse birth outcomes in Shanghai, China, and analyze the correlation between the prevalence of AMA and the prevalence of these adverse birth outcomes.MethodsA total of 173,690 birth data was collected from four regionally influential hospitals in Shanghai from 2010 to 2023. The prevalence of adverse birth outcomes (including preterm birth, low birth weight, small for gestational age, and birth defect) was calculated. Joinpoint regression analysis was conducted to estimate the temporal trends and calculate the Average Annual Percentage Change (AAPC) and Annual Percentage Change (APC) of adverse birth outcomes and AMA. A correlation study design was employed to evaluate the population-level correlation between the prevalence of adverse birth outcomes and AMA.ResultsThere were 13,445 (7.74%) preterm birth (PTB), 10,226(5.89%) low birth weight (LBW), 7,152 (4.12%) small for gestational age (SGA), and 3,227 (1.86%) birth defects (BD) over the past 14 years. Sex differences were observed across different adverse birth outcomes. The prevalence of PTB (AAPC = 0.87%, P = 0.045) and LBW (AAPC = 2.94%, P < 0.001) showed significant upward trends from 2010 to 2023. The prevalence of SGA (APC = 2.42%, P < 0.001) presented an increasing trend from 2012 to 2023, while the prevalence of BD (AAPC = 5.73%, P = 0.227) remained relatively stable. The rate of AMA (AAPC = 10.14%, P < 0.001) also showed a significant upward trend from 2010 to 2023. Additionally, this study found a strong positive correlation between the rate of AMA and the prevalence of LBW (r = 0.89, P < 0.001) and BD (r = 0.92, P < 0.001). Moderate positive correlations were observed between AMA and the prevalence of PTB (r = 0.61, P = 0.022) and SGA (r = 0.75, P = 0.002).ConclusionThe overall prevalence of PTB, LBW, and SGA has shown an increasing trend, aside from BD. AMA also has risen annually and was significantly associated with these adverse birth outcomes. This suggests that enhancing support for advanced-age mothers could potentially mitigate adverse birth outcomes. Besides, gender differences on these adverse birth outcomes demonstrate the implementation of gender-specific healthcare strategies.